Understanding the Narratives Explaining the Ukrainian Crisis: Identity Divisions and Complex Diversity in Ukraine - Smoor Lodewijk (Acta Universitatis Sapientiae: European and Regional Studies, 2017)
The central argument of this paper is that radical and opposing interpretations of the Ukrainian conflict in politics and media should be studied as offspring of broader narratives. These narratives can be better understood by examining the national identity of Ukraine. Since Ukrainian national identity shows a high degree of diversity, it offers a rich source of arguments for any party wanting to give an interpretation of the present Ukrainian crisis. Narratives explaining the crisis often ignore this complex diversity or deliberately use elements from it to construct the ‘desired’ narrative.